Circulating fatty acids, genetic susceptibility and hypertension: a prospective cohort study - Lu, Lingling; Gu, Xiaoli; Yang, Daheng; Wang, Bingjian; Long, Guangfeng (Frontiers in Nutrition, 2024)
Background: Combining genetic risk factors and plasma fatty acids (FAs) can be used as an effective method of precision medicine to prevent hypertension risk.: A total of 195,250 participants in the UK Biobank cohort were included in this study from 2006--2010. Polygenic risk scores (PRSs) were calculated for hypertension using single-nucleotide polymorphisms (SNPs). Concentrations of plasma FAs, including polyunsaturated fatty acids (PUFAs), monounsaturated fatty acids (MUFAs) and saturated fatty acids (SFAs), were tested by nuclear magnetic resonance. The Cox model was used to test for the main effects of PRS, different plasma FAs and their joint effects on hypertension. Relative excess risk due to interaction (RERI) and the attributable proportion due to interaction (AP) were used to test the additive interaction.